PENGARUH PENGENDALIAN INTERNAL, GOOD CORPORATE GOVERNANCE, DAN SISTEM PENGUKURAN KINERJA TERHADAP PENCEGAHAN FRAUD (Studi kasus pada Instansi Pemerintah di Daerah Istimewa Yogyakarta) - Aprila Firli Damayanti; Anita Primastiwi (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2021)
This study aims to examine the effect of internal control, good corporate governance, and performance measurement system on fraud prevention in government agencies of the Special Region of Yogyakarta. The method used in this research a quantitative method in the form of primary data using a questionnaire. The sampling technique used was the purposive sampling method. The population in this study were permanent employees and non-permanent employees in the Special Region of Yogyakarta with a sample size of 80 respondents. Data collection is done by giving questionnaires directly to respondents via a google form. The data in this study were tested using the Software Statistical Package for Social Sciences (SPSS) version 20. The results of this study indicate that internal control does not affect and fraud prevention, while good corporate governance and performance measurement system have a positive effect on fraud prevention.Keywords: Internal Control, Good Corporate Governance, Performance Measurement System, Fraud Prevention